A regioselective synthesis of 7-methyl juglone and its derivatives. Issue 1 (22nd December 2021) - Cui, Jiahua; Li, Shaoshun; Jia, Jinping
Abstract: 7-Methyl juglone as a naturally occurring naphthoquinone showed striking antibacterial, antifungal, antivirus and anticancer activity. Its derivatives had also been characterized as key intermediates in the preparation of natural naphthoquinones and anthraquinones. Herein, we reported a regioselective synthesis of 7-methyl juglone via the construction of fused polycyclic systems. The key steps of the strategy involved Stobbe condensation of 2, 5-dimethoxy benzaldehyde with diethyl succinate, intramolecular cyclization, reduction, acid-facilitated debenzylation and further cerium(IV) ammonium nitrate-mediated oxidation. Compared with the reported methods employing Birch conditions in liquid ammonia or Friedel-Crafts cycloacylation with melting heat of aluminum salts, the reaction conditions in the new synthetic route were milder and suitable for large scale preparations. In addition, all of the starting materials in the synthesis were readily available. It has great implications for the design and synthesis of structurally asymmetric naphthoquinones derivatives. Graphical Abstract: UF0001